Aneka Fungsi Bahasa Syair- Syair Lagu Ismail Marzuki - I Dewa Putu Wijana (Deskripsi Bahasa, 2018)
This article intends to reveal various language functions consisted in Ismail Marzuki’s song lyrics in the frame of the widely known Jakobson’s language function theory. By using data gathered from various sources, the research findings shows that Ismail Marzuki’s song lyrics are dominated by the use of language which is exploited to bear poetic function in order to enable the audiences experiencing the song’s messages and other language functions aesthetically. All Marzuki’s song lyrics concern with extralinguistic world. Accordingly, it is not surprising that none of the song lyric is used to convey metalinguistic function for explaining the internal structure of a language.